2022
DOI: 10.1021/acs.analchem.1c05378
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Purification of Plasma Extracellular Vesicles Using Titanium Dioxide Microparticles for Depicting the Metabolic Signatures of Diabetic Retinopathy

Abstract: Extracellular vesicle (EV) cargos with regular fluctuations hold the potential for providing chemical predictors toward clinical diagnosis and prognosis. A plasma sample is one of the most important sources of circulating EVs, yet the technical barrier and cost consumption in plasma-EV isolation still limit its application in disease diagnosis and biomarker discovery. Here, we introduced an easy-to-use strategy that allows selectively purifying small EVs (sEVs) from human plasma and detecting their metabolic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Non-specific isolation: (D) TiO 2 -lipid affinity Reproduced with permission. 153 Copyright 2022, American Chemical Society. (E) DSPE inserting.…”
Section: Aptamer Based Ev Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specific isolation: (D) TiO 2 -lipid affinity Reproduced with permission. 153 Copyright 2022, American Chemical Society. (E) DSPE inserting.…”
Section: Aptamer Based Ev Isolationmentioning
confidence: 99%
“…Hu et al employed this user-friendly strategy selectively isolating EVs and detecting their metabolic alternations (Figure 6D). 153 Zhang and co-workers reported a similar TiO 2 -mediated EV isolation strategy from a small volume of plasma, where they simultaneously profiled proteins and metabolites. 161 Another research group utilized this strategy for reversible EV isolation, achieving high recovery rates (93.4%) using an alkaline solution.…”
Section: Peptides Based Ev Isolationmentioning
confidence: 99%
“… 71 Recently, an effective EV capture system using Titanium Dioxide microparticles has been designed to facilitate plasma-based liquid biopsies to understand the metabolic signatures of diabetic retinopathy. 72 …”
Section: How Potential Of Metabolomics Of Extracellular Vesicles In C...mentioning
confidence: 99%
“…71 Recently, an effective EV capture system using Titanium Dioxide microparticles has been designed to facilitate plasma-based liquid biopsies to understand the metabolic signatures of diabetic retinopathy. 72 Figure 3 Application of EV metabolomics. The analysis of EVs metabolomics usually requires for several steps, including isolation of EVs, mass spectrometry analysis of inner metabolites and analysis of the metabolic maps.…”
Section: How Potential Of Metabolomics Of Extracellular Vesicles In C...mentioning
confidence: 99%
“…Proteins on EVs exhibit distinct functions compared with proteins in vesicle-free states. Previous works have demonstrated that the diagnostic value of proteins involved in EVs is different from the corresponding proteins presented in plasma in vesicle-free states. , Recently, some groups have used membrane affinity molecules to isolate EVs based on their high affinity toward the phospholipid bilayer of EVs, which is applicable to capture all EVs regardless of size and protein composition. For instance, Fang’ s group employed distearoyl phosphoethanolamine (DSPE)-modified magnetic beads to capture EVs and simultaneously detected the membrane protein and RNA with aptamer-assisted PCR .…”
mentioning
confidence: 99%